Thermal and non-thermal DM production in non-standard cosmologies: a mini review - Arcadi, Giorgio (Frontiers in Physics, 2024)
We provide a short review of some aspects of Dark Matter production in non Standard Cosmology. Considering the simplest Higgs portal model as definite particle physics setup, we consider the impact on the parameter space corresponding to the correct relic density, and the complementary experimental constraints, of the presence, during thermal production, of an exotic component dominating the energy density of the Universe. In the second part of the work we will focus on the case that such exotic component satisfies the equation of state of matter and it can produce DM non-thermally. 'Early Matter Domination period', due, for examples, to heavy metastable particles. On a